2008
DOI: 10.1086/590234
|View full text |Cite
|
Sign up to set email alerts
|

Spectropolarimetric Observation of an Emerging Flux Region: Triggering Mechanisms of Ellerman Bombs

Abstract: A high spatial resolution observation of an emerging flux region ( EFR) was made using a vector magnetograph and a H Lyot filtergraph with the Domeless Solar Telescope at Hida Observatory on 2006 October 22. In H wing images, we could see many Ellerman bombs ( EBs) in the EFR. Observations in two modes, slit scan and slit fixed, were performed with the vector magnetograph, along with the H filtergraph. Using the H wing images, we detected 12 EBs during the slit scan observation period and 9 EBs during the slit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 27 publications
8
69
0
4
Order By: Relevance
“…Selected recent Ellerman bomb studies of particular relevance here, in addition to the comprehensive study of Georgoulis et al (2002), are those by Pariat et al (2004Pariat et al ( , 2007, Isobe et al (2007), Watanabe et al (2008), Matsumoto et al (2008), Hashimoto et al (2010), Morita et al (2010), and Guglielmino et al (2010). These studies provide evidence that the Ellerman bomb phenomenon occurs at sites of and is due to magnetic reconnection, and characteristically has elongated shapes reminiscent of the "chromospheric anemone jets" of Shibata et al (2007).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Selected recent Ellerman bomb studies of particular relevance here, in addition to the comprehensive study of Georgoulis et al (2002), are those by Pariat et al (2004Pariat et al ( , 2007, Isobe et al (2007), Watanabe et al (2008), Matsumoto et al (2008), Hashimoto et al (2010), Morita et al (2010), and Guglielmino et al (2010). These studies provide evidence that the Ellerman bomb phenomenon occurs at sites of and is due to magnetic reconnection, and characteristically has elongated shapes reminiscent of the "chromospheric anemone jets" of Shibata et al (2007).…”
Section: Introductionmentioning
confidence: 79%
“…In particular, Pariat et al (2004Pariat et al ( , 2007 and Watanabe et al (2008) found evidence for undulating "serpentine" field topologies with Ellerman bombs formed at the dip of field lines (called "bald patches" in the French literature), where the fields are nearly antiparallel. The fact that Ellerman bombs are reported to occur only in emerging flux regions speaks for an antiparallel reconnection scenario.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of flux emergence (first day) there is no single magnetic inversion line, but small (≈ 2 Mm) individual bipoles appear all over the AR in between the growing magnetic concentrations at the edges of the emerging flux Bernasconi et al, 2002). The small-scale pattern is suggestive of undulatory (serpentine) flux formed of an alternating series of small Ω and U-loops breaking through the photosphere (Strous et al, 1996;Pariat et al, 2004;Watanabe et al, 2008). These small-scale flux emergence sites may be recurrent and they may appear with a wavelike regularity (with a = 8 Mm) in between the two main opposite polarity concentrations (Strous and Zwaan, 1999).…”
Section: Main Laws and Intrinsic Characteristics Of Large-scale Magnementioning
confidence: 99%
“…From a set of identified serpentine lines in their model, Pariat et al (2004) found that the distance between successive EBs along the undulating flux tubes has a peak around 3 Mm and a cutoff for values smaller than 2 Mm. Watanabe et al (2008) reported that magnetic fields around EBs are undulatory with a characteristic wavelength of ≈4 Mm. These sizes are larger than the convective scales for granulation (≈1 Mm) or less than supergranulation (≈10 Mm) and are indicative of the presence of some instability.…”
Section: Introductionmentioning
confidence: 99%